Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1086/652701
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Cross‐Reactive Immunogenicity of Candidate AS03‐Adjuvanted Prepandemic H5N1 Influenza Vaccines: A Randomized Controlled Phase 1/2 Trial in Adults

Abstract: Humoral responses against the adjuvanted 3.75-microg hemagglutinin antigen vaccines from both manufacturing sites fulfilled European and US licensure criteria for immunogenicity for influenza vaccines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
52
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 25 publications
4
52
0
Order By: Relevance
“…The AS03 adjuvant system is specifically designed to increase innate immune responses by enhancing migration of monocytes and macrophages and by increasing localized production of a range of cytokines and chemokines intramuscularly at the site of injection and in the draining lymph nodes. Thus, the higher local reactogenicity observed in the HiP-AS group than in the HiP group may be secondary to these enhanced innate immune responses elicited at the site of injection and therefore is not unexpected (32,33). This was consistently observed in studies evaluating AS03-adjuvanted influenza vaccines, in which higher local reactogenicity was observed with adjuvanted versus nonadjuvanted vaccines (34,35).…”
Section: Discussionmentioning
confidence: 72%
“…The AS03 adjuvant system is specifically designed to increase innate immune responses by enhancing migration of monocytes and macrophages and by increasing localized production of a range of cytokines and chemokines intramuscularly at the site of injection and in the draining lymph nodes. Thus, the higher local reactogenicity observed in the HiP-AS group than in the HiP group may be secondary to these enhanced innate immune responses elicited at the site of injection and therefore is not unexpected (32,33). This was consistently observed in studies evaluating AS03-adjuvanted influenza vaccines, in which higher local reactogenicity was observed with adjuvanted versus nonadjuvanted vaccines (34,35).…”
Section: Discussionmentioning
confidence: 72%
“…Two different doses of AS03 (AS03A, containing the full dose of 2.5% squalene and 2.5% ␣-tocopherol, versus AS03B, containing a half dose) were evaluated in another influenza vaccine clinical trial, where it was concluded that while initial immune responses elicited by the two different adjuvant doses were equivalent, the durability of the response measured at 182 days postvaccination was somewhat better with the higher adjuvant dose (21). Furthermore, the 41-to 64-year-old age group showed significantly reduced antibody responses at the lower adjuvant dose.…”
Section: Figmentioning
confidence: 99%
“…Both of these adjuvants contain squalene at ϳ2.5% (vol/vol) in the final vaccine formulation (13). However, until recently, only a few reports regarding the motivation for selecting this squalene concentration were published (9,21,25). Moreover, a recent study showed that dilution of MF59 did not compromise the immune response in a pandemic influenza vaccine clinical trial (20).…”
mentioning
confidence: 99%
“…[41][42][43][44] A recently published phase 2 open-label study that includes adults older than 61 y assessed the immune response elicited after two single or two double doses of ASO3 adjuvanted H5N1 vaccine administered 21 d apart compared with unadjuvanted influenza vaccine. Two injections of a single dose of 3.75mg H5N1 ASO3 adjuvanted vaccine were shown to elicit high levels of HA and neutralizing antibodies and cell mediated immunity was maintained for six months after vaccination.…”
Section: New Vaccinesmentioning
confidence: 99%